Not “Dressed Like a Philosopher”: Tactful Statesmanship in Utopia and the Epigrams - Hebert, Louie Joseph (Moreana, 2021)
This paper argues that the mode of statesmanship recommended in Utopia provides the framework for the Epigrams. While Utopia demonstrates the need for artful indirection by exposing the vices of a man too proud to adopt it, the Epigrams exhibit More's preparation for and practice of a tactfully philosophic statesmanship.